PAINTING TECHNIQUES OF 1ST ART THERAPY IMPORTANCE OF APPLICATION - Tojinorova Laylo Odil qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation: this article covers current issues of art therapy, which includes all types of art, as well as the importance of applying art therapy techniques in painting, and in addition to various forms of art.